2003
DOI: 10.17221/4145-pse
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of frost resistance in varieties of common buckwheat (Fagopyrum esculentum Moench)

Abstract: The aim of this study was to determine the most sensitive growth stage of common buckwheat to frost temperatures and evaluate differences in frost resistance among varieties. A modified field-laboratory method was utilised for the study on four varieties of common buckwheat. The lethal temperature (LT 50 ) was determined for all variants. The critical time of frost action (Lt 50 ) was determined for the lethal temperature and for the most sensitive growth stage. Buckwheat is most sensitive to frost temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Both of these species were slow growing throughout the relatively cool and dry early growing season in 2009 (Table 3), and buckwheat was moderately susceptible to early frost. Buckwheat is often used as a summer cover crop or later planted main crop due to its susceptibility to frost, especially during seedling growth (Kalinova and Moudry, 2003); thus, buckwheat may not be a suitable species for use as a spring‐sown cover crop in the western Corn Belt. Given these results, buckwheat was replaced in all mixtures with Idagold mustard in 2010 and 2011.…”
Section: Resultsmentioning
confidence: 99%
“…Both of these species were slow growing throughout the relatively cool and dry early growing season in 2009 (Table 3), and buckwheat was moderately susceptible to early frost. Buckwheat is often used as a summer cover crop or later planted main crop due to its susceptibility to frost, especially during seedling growth (Kalinova and Moudry, 2003); thus, buckwheat may not be a suitable species for use as a spring‐sown cover crop in the western Corn Belt. Given these results, buckwheat was replaced in all mixtures with Idagold mustard in 2010 and 2011.…”
Section: Resultsmentioning
confidence: 99%
“…While low temperature (below 10 °C) generally delays or inhibits the flowering (Bjorkman 2000), high temperature (above 30 °C) is reported to cause abortion of ovule and embryo sac malformation (Gang and Yu 1998). It has been observed that exposure of buckwheat plant to frost conditions for 4 to 6 h to temperatures between − 1 and − 3 °C during emergence and at the end of growing season generally ceases the growth and leads to heavy yield losses (Kalinova and Moudry 2003). If conditions are favorable, seedling emerges 4-5 days after sowing and plants show profuse vegetative growth from 3rd to 6th week.…”
Section: Growth Development and Agronomic Attributesmentioning
confidence: 99%
“…Many of the floral resources investigated, such as white rocket, were not "conventional" in that some may be more suitable in areas of low water availability (Qasem, 2007;Schleser et al, 1989). As with parasitoids in many other studies (Araj & Wratten, 2015;Araj, Wratten, Lister, & Buckley, 2006;Araj et al, 2008;Tylanakis et al, 2004;Wade & Wratten, 2007) prefers a temperate climate (Joshi & Paroda, 1991;Siracusa, Gresta, Sperlinga, & Ruberto, 2017), has a short flowering season (Sattell, Dick, Karow, & McGrath, 1998) and is susceptible to frost (Kalinova & Moudry, 2003). Therefore, it may be more suitable to use more robust species.…”
Section: Discussionmentioning
confidence: 99%
“…As with parasitoids in many other studies (Araj & Wratten, ; Araj, Wratten, Lister, & Buckley, ; Araj et al., ; Tylanakis et al., ; Wade & Wratten, ), buckwheat substantially increased A. colemani longevity, potential fecundity and parasitism of the target pest compared to the other floral resources evaluated. However, buckwheat prefers a temperate climate (Joshi & Paroda, ; Siracusa, Gresta, Sperlinga, & Ruberto, ), has a short flowering season (Sattell, Dick, Karow, & McGrath, ) and is susceptible to frost (Kalinova & Moudry, ). Therefore, it may be more suitable to use more robust species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation